Diagnostic value of Ep300 and FOXO4 proteins in acute ischemic stroke: preliminary findings from a case-control study - Bülbül,Emre; Toker,İbrahim; Dana,Halime; Doğan,Mehmet; Mercan,İbrahim; Çoşkun Işık,Burcu; Şener,Elif Funda (PeerJ, 2025)
Background Stroke is a leading cause of death and disability worldwide, and there is still a lack of specific and sensitive biomarkers for its diagnosis. Objective This study aimed to investigate the diagnostic value of FOXO4 and Ep300 proteins in acute ischemic stroke patients who visited the emergency department. Methods Patients were consecutively included in the study. The amount of Ep300 and FOXO4 proteins was determined using an enzyme-linked immunosorbent assay (ELISA). Receiver operator characteristic (ROC) analyses of FOXO4 and Ep300 proteins were performed. Results The study was conducted on a total of 39 acute ischemic stroke patients, 17 females and 22 males, with a mean age of 66.9 ± 11 years. Seventeen females and 23 male control were also included. The discriminative ability of Ep300 protein was not statistically significant (p value = 0.380). FOXO4 protein had moderate discriminative ability (AUC value = 0.705 and p value = 0.002). When the cut-off value for FOXO4 protein was accepted as > 1.15, the sensitivity was 74.29%, the specificity was 64.52%, the positive predictive value was 70.3%, the negative predictive value was 69%, the positive likelihood ratio was 2.09, and the negative likelihood ratio was 0.4. Conclusions The study’s findings suggest that FOXO4 protein could potentially serve as a valuable biomarker in the diagnosis of stroke in acute ischemic stroke patients.
Keywords: Ischemic stroke; Foxo4 protein; Ep300 protein; Human